Rancang Bangun Sistem Informasi Penjualan Untuk Startup Bisnis Cafe Online Pada Cafe di Daerah Caruban Jawa Timur Berbasis Web - Rahmawati, Endra; Nugroho, Riski Wahyu; Wulandari, sri hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The high consumers interest of caruban city to make purchase in the café make the café always crowded by customers. In the caruban region itself there is no online sales system for café or can be called café online. All sales and promotional  processes are done traditionally. Customers come to café and order food, for promotional café businessman spread brochures and word of mouth.Business process on caruban online café is a sales system that capable to order online in caruban city via web browser. System that can meet customer needs to order food anytime and anywhere which  is still within the city of caruban that have online order feature. Of course with many interest of the customers who make transactions through the café online will also increase revenue startup owner. With advertising and premium access to café owners, and Rp.200 fee to the café owner for each transaction.Based on the above problems the solution is the design of caruban café online application system. This system can provide information the capacity of the café is full, can reach customers who are away from the café location, can provide variant menu and promoting their menu due to limited capital. All of the system information is tested and result is 100% work for owner startup.Keywords: System information, Sales, Online Cafe, Caruban City